Connected Mathematics Project in Vocational School: A Teaching Quality that Improves student's Mathematical Reasoning and Resilience - Silfi Audina; Dede Salim Nahdi; Mohamad Gilar Jatisunda; Ujiati Cahyaningsih (Papanda Publisher, 2023)
Mathematical reasoning and resilience are essential skills that students need to master in the process of learning mathematics. Both of these skills can be cultivated through instructional models that stimulate students to construct their own knowledge by connecting learning to the real world. One instructional model characterized by these aspects is the Connected Mathematics Project (CMP). Consequently, the purpose of this study is to analyze the effectiveness of the CMP instructional model in enhancing mathematical reasoning and resilience abilities. This research employs a quantitative approach utilizing a quasi-experimental design, specifically the nonequivalent posttest-only control group design. The study was conducted in one vocational high school in Majalengka. Sample selection was carried out using the cluster random sampling technique, resulting in a total of 18 students in the experimental group and 18 students in the control group. The research instruments comprised a mathematical reasoning ability test consisting of three open-ended test items and a mathematical resilience questionnaire. The findings of this study indicate that: (1) students' mathematical reasoning abilities in the CMP instructional model are higher compared to those in conventional instruction; (2) the average percentage of students' resilience attitudes in the CMP instructional model is higher than those in conventional instruction; and (3) CMP instruction is effective in improving both mathematical reasoning and resilience abilities among vocational high school students.